2016
DOI: 10.1111/jcpe.12538
|View full text |Cite
|
Sign up to set email alerts
|

Host‐derived salivary biomarkers in diagnosing periodontal disease: systematic review and meta‐analysis

Abstract: There is currently limited evidence to confirm the diagnostic capability of salivary biomarkers in the clinical assessment of periodontal disease. Notwithstanding, the summary findings showed the growing importance of salivary biomarker, and can guide larger, well-controlled, diagnostic accuracy studies. Likewise, although not conclusive, MIP-1α, IL-1β, and IL-6 may be promising biomarkers for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 42 publications
3
42
1
1
Order By: Relevance
“…They found that macrophage inflammatory protein‐1a had excellent diagnostic accuracy (sensitivity of 0.95, specificity of 0.93). Interleukin‐1b (sensitivity of 0.54‐0.88, specificity of 0.55‐1) and interleukin‐6 (sensitivity of 0.59‐0.88, specificity of 0.60‐0.97) showed acceptable diagnostic values . These markers presented higher sensitivity/specificity values than salivary LDH assessed in our study (sensitivity of 0.63, specificity of 0.57).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…They found that macrophage inflammatory protein‐1a had excellent diagnostic accuracy (sensitivity of 0.95, specificity of 0.93). Interleukin‐1b (sensitivity of 0.54‐0.88, specificity of 0.55‐1) and interleukin‐6 (sensitivity of 0.59‐0.88, specificity of 0.60‐0.97) showed acceptable diagnostic values . These markers presented higher sensitivity/specificity values than salivary LDH assessed in our study (sensitivity of 0.63, specificity of 0.57).…”
Section: Discussioncontrasting
confidence: 49%
“…Recently, De Lima et al systematically evaluated salivary biomarkers in the diagnosis of periodontal disease based on the sensitivity and specificity information . They found that macrophage inflammatory protein‐1a had excellent diagnostic accuracy (sensitivity of 0.95, specificity of 0.93).…”
Section: Discussionmentioning
confidence: 99%
“…The source and dynamics of these neuropeptides should be further investigated as they could serve as possible diagnostic parameters to discriminate between periodontal health and disease. They might contribute to salivary biomarker research in periodontitis, helping to find a more innovative way of assessing clinical disease as well as new approaches in the understanding of underlying pathogenic mechanisms of periodontitis …”
Section: Discussionmentioning
confidence: 99%
“…However, the great number of potential markers and individual differences in the microbiome makes it difficult to uncover those related to complex diseases such as periodontitis. Markers should be specific and sensitive enough to discriminate between periodontal health and disease and ideally reflect inflammatory status, tissue destructive processes, tissue remodeling, and microbiologic aspects …”
mentioning
confidence: 99%
See 1 more Smart Citation